Digital Siege - Karadogan Doruk, Sevimece; Mengu, Seda; Ulusoy, Ebru (Istanbul University Press, 2021)
Digitalization is prevalent in almost every field of life in today's world. There is no escape from its impacts. But, it is getting increasingly important to investigate its positive and negative aspects to build a digital culture that benefits, rather than hurts and divides societies and people. This book addresses a theme of growing importance in multiple disciplines, such as communication, business, political science, sociology. It aims to understand how digitalization has been transforming our world and identities. Academic interest in this topic is due to an increasing need to understand these transformations' details and the meaning of these transformations in the big scheme of things. This book was inspired by a desire to draw together an academic interest in this topic to investigate the meaning and impacts of digitalization and the "new" digital culture. We invited authors from different areas to write chapters that contribute to exploring how digitalization affects their field and its consequences. Each chapter in this book seeks to contribute to the conceptual understanding of one or more dimensions of digitalization. It investigates from a multidisciplinary perspective the 'what's 'how's of digitalization, and tries to understand the advantages and disadvantages of it for society, various institutions, and individual consumer citizens.